2004
DOI: 10.1056/nejmoa031855
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Therapies for Proliferative Lupus Nephritis

Abstract: For patients with proliferative lupus nephritis, short-term therapy with intravenous cyclophosphamide followed by maintenance therapy with mycophenolate mofetil or azathioprine appears to be more efficacious and safer than long-term therapy with intravenous cyclophosphamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
468
8
25

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 743 publications
(515 citation statements)
references
References 17 publications
14
468
8
25
Order By: Relevance
“…A recent trial by Contreras et al [22] sheds light on the relative efficacy of maintenance regimens using either MMF, AZA, or continued i.v. CYC in severe LN.…”
Section: Resultsmentioning
confidence: 99%
“…A recent trial by Contreras et al [22] sheds light on the relative efficacy of maintenance regimens using either MMF, AZA, or continued i.v. CYC in severe LN.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy and tolerability of mycophenolate mofetil combined with prednisolone have been demonstrated in Chinese patients with class IV lupus nephritis, who showed a Ͼ90% response rate and a 6.3% incidence of serum creatinine doubling over a median followup of 63 months (13). Data from studies in the US, which included high-risk subjects such as African American and Hispanic patients, showed a higher response rate (though still suboptimal, at 52%) and a lower relapse rate with mycophenolate mofetil and prednisone, compared with CYC-based induction or maintenance treatment, respectively (6,14). A cohort study in the UK has demonstrated a favorable response rate and tolerability profile with mycophenolate mofetil and prednisone as the primary treatment in Caucasian patients (4).…”
mentioning
confidence: 99%
“…CYC appears to have an unacceptable safety profi le for long-term use in maintenance therapy given the risks of impaired fertility, alopecia, and hemorrhagic cystitis. 25,26 A study by Contreras et al randomized 59 patients to maintenance therapy with either quarterly CYC infusions, oral AZA, or oral MMF continued from 1 to 3 years. 26 AZA and MMF had higher event-free survival than CYC for the composite endpoint of death and chronic renal failure, and also lower risk of relapse.…”
Section: Maintenancementioning
confidence: 99%
“…25,26 A study by Contreras et al randomized 59 patients to maintenance therapy with either quarterly CYC infusions, oral AZA, or oral MMF continued from 1 to 3 years. 26 AZA and MMF had higher event-free survival than CYC for the composite endpoint of death and chronic renal failure, and also lower risk of relapse. The safety profi le was also superior for the AZA and MMF arms compared with CYC, with lower rates of hospitalization, amenorrhea, and infection.AZA and MMF have been found to have similar effi cacy in several randomized trials.…”
Section: Maintenancementioning
confidence: 99%
See 1 more Smart Citation